Paralytic Ileus in Vegetarian with Pneumonia Infection - Khaira Utia Yusrie (The Indonesian Society for Digestive Endoscopy, 2004)
Paralytic ileus which is commonly found in clinical practice is referred to clinical syndrome of transportation disturbance of the intestinal lumen content due to various etiology and underlying condition. It has been considered a transient gastrointestinal syndrome with good prognosis. Most cases respond well to conservative management. However, inappropriate diagnostic approach and management will result in severe complication leading to death such as septicemia and perforation. We reported a case of paralytic ileus in young male who is vegetarian with pneumonia infection as the suspected underlying etiology. Radiological examination of the abdomen in three position (upright, supine and lateral) showed dilated gaster and duodenum with minimal air fluid level, no herring bone appearance and absent of free intraperitoneal air. The laboratory result also showed low level of vitamin B12 which might be due to his lactovegetarian diet habit. Management including supportive therapy such as decompression, fasting, adequate parenteral nutrition, fluid balance and treatment of pneumonia as the underlying cause of paralytic ileus had been resulted in good clinical response. Keywords: Paralytic ileus, pneumonia, treatment